Soviet Musical Avant-Garde in the Context of Time (in the mid. 1950s – 1980s): Historical and Cultural Studies and Philosophical Aspects - O. V. Andreeva (Дискурс, 2020)
Introduction. Interest in the work of avant-garde artists does not wane as they move away from the 20th century. This is due to the fact that the musical avant-garde, becoming a sign of the time, reflected the most important trends of the outgoing era. In the paper, the Soviet musical avant-garde is considered in the historical, cultural and philosophical aspect in the context of the historical era, which determines the novelty of the study. An aspect of novelty is the analysis of music as a sphere of intercultural communication.Methodology and sources. The research methodology is based on the analysis of sources and literature, taking into account interdisciplinary approaches. A special role in the understanding of the theoretical aspects of the problem play the work of musicologists Yu. N. Kholopova, V. N. Kholopova, V. S. Price, R. L. Pospelova, A. I. Demchenko. Among the sources highlighted in cinema, photo- and phonodocuments, which depicts a vivid image of the era. The interviews with composers, which presents a wide canvas of social and musical life (A. Schnittke, A. Ivashkina entry and volkonskii, recording E. Dubinets) are of considerable interest. Historical, comparative, systematic and semiotic methods of analysis were used. Applies a comprehensive approach (formation and civilization methods of research and the Annales school). This allows for a new approach to the historical era of the middle1950s – 1980s.Results and discussion. Postwar culture is examined as a single space, in which a special role was played by the impulses of the “thaw”. They gave cultural phenomena such inertial dynamics, which preserves the spiritual maturity of society and produced changes of the 1990s, the results of the study show that in contrast to the political and socio-economic processes, cultural life in these years continued to feel the pulses of the “thaw”. Retaining the inertial dynamics of development, cultural processes have been far from stagnation, which casts doubt on the overall rating this time as the “era of stagnation”. This allows you to put a discussion question on the revision of the political clichés in relation to the period of the middle 1960s – 1980s in the Soviet Union as the “era of stagnation”.Conclusion. Soviet avant-garde, expressing the spirit of the time, represents the unique phenomenon in which reflected global trends, and the uniqueness of national culture. Experience avant-garde shows that cultural processes of the epoch middle 1950s – 1980s had a high development dynamics. The study of this period, especially in its spiritual sphere, requires interdisciplinary approaches and the use of modern, including foreign methods. Interest methods of the Annales school in its historical retrospect and the “new cultural history”.